1998
DOI: 10.1172/jci1457
|View full text |Cite
|
Sign up to set email alerts
|

Altered pattern of TCR/CD3-mediated protein-tyrosyl phosphorylation in T cells from patients with systemic lupus erythematosus. Deficient expression of the T cell receptor zeta chain.

Abstract: Cellular immunity aberrations in patients with SLE are underscored by the abnormal early Ag receptor-mediated lymphocyte signal transduction pathway. To further characterize the T cell receptor (TCR)/CD3-initiated signaling defects, we studied 22 patients with SLE, 12 patients with other systemic rheumatic diseases, and 14 normal donors. The early (1 min) TCR/CD3-mediated tyrosine phosphorylation of cellular proteins with a molecular size between 36 and 64 kD was increased in 15 of 21 SLE patients, compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
228
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(246 citation statements)
references
References 39 publications
17
228
0
1
Order By: Relevance
“…There were many reports about TCR/CD3 defects in SLE patients. 23,38,39 In our study, we also found the TCRs pathways, TCRa, TCRd, and Zap-70 associated protein kinase 70 kDa) had lower expression in SLE patients. So, an inverse relationship between TSA-1 and CD3 expression on thymocytes may reflect abnormal activated lymophocytes in SLE patients.…”
Section: Discussionsupporting
confidence: 69%
“…There were many reports about TCR/CD3 defects in SLE patients. 23,38,39 In our study, we also found the TCRs pathways, TCRa, TCRd, and Zap-70 associated protein kinase 70 kDa) had lower expression in SLE patients. So, an inverse relationship between TSA-1 and CD3 expression on thymocytes may reflect abnormal activated lymophocytes in SLE patients.…”
Section: Discussionsupporting
confidence: 69%
“…Dysregulation of the BCR-mediated signaling pathway is likely to result in the breakdown of peripheral B cell tolerance and the development of SLE. In the case of the T cell receptor, the zeta chain of the CD3 complex is aberrantly expressed in a subset of SLE patients, which has been implicated in tolerance disruption (48,49). In fact, the phosphorylation patterns of several proteins of T and B lymphocytes are altered in patients with SLE (20)(21)(22)47,50), which suggests that signaling pathways, including protein kinases and phosphatases, are defective in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…T-cells with suppressed zeta chain have been demonstrated to exhibit diminished proliferation and production of cytokines. Decreased zeta chain expression occurs in other disease states, including chronic infections and systemic lupus erythematosus, where deficient zeta chain expression has been proposed to aberrantly modulate T-cell functions (Liossis et al, 1998).…”
Section: Discussionmentioning
confidence: 99%